Two Intracellular Symbiotic Bacteria from the Mulberry Psyllid Anomoneura mori (Insecta, Homoptera) - Fukatsu, Takema (American Society for Microbiology, 1998)
We characterized the intracellular symbiotic bacteria of the mulberry psyllid Anomoneura mori by performing a molecular phylogenetic analysis combined with in situ hybridization. In its abdomen, the psyllid has a large, yellow, bilobed mycetome (or bacteriome) which consists of many round uninucleated mycetocytes (or bacteriocytes) enclosing syncytial tissue. The mycetocytes and syncytium harbor specific intracellular bacteria, the X-symbionts and Y-symbionts, respectively. Almost the entire length of the bacterial 16S ribosomal DNA (rDNA) was amplified and cloned from the whole DNA of A. mori, and two clones, the A-type and B-type clones, were identified by restriction fragment length polymorphism analysis. In situ hybridization with specific oligonucleotide probes demonstrated that the A-type and B-type 16S rDNAs were derived from the X-symbionts and Y-symbionts, respectively. Molecular phylogenetic analyses of the 16S rDNA sequences showed that these symbionts belong to distinct lineages in the γ subdivision of the Proteobacteria. No 16S rDNA sequences in the databases were closely related to the 16S rDNA sequences of the X- and Y-symbionts. However, the sequences that were relatively closely related to them were the sequences of endosymbionts of other insects. The nucleotide compositions of the 16S rDNAs of the X- and Y-symbionts were highly AT biased, and the sequence of the X-symbiont was the most AT-rich bacterial 16S rDNA sequence reported so far.